28. A multicentre QA study on 4DCT and IMRT/VMAT techniques for lung stereotactic treatments using the 008A CIRS 4D phantom. (December 2016) - Lambrecht, M.; Hurkmans, C.
Abstract : Introduction: To determine stereotactic treatments accuracy in the institutions participating in the Phase II EORTC trial: Lungtech, we have performed end-to-end tests investigating both 4D computed tomography (4D-CT) and IMRT/VMAT technique under static and dynamic conditions. Methods: All centres audited (6) performed 3D-CTs and 4D-CTs on the same CIRS008A phantom. The phantom was successively scanned using two film inserts, one with a 15mm diameter target (15 mmd) and the other carrying a 25 mm diameter target (25 mmd). Three motions were tested: 20 bpm/15 mm amplitude (A), 10 bpm/15 mmA, and 15 bpm/25 mmA. We thus developed a test procedure to evaluate the impact of motion on the target volume and motion as determined using the available binned CT data. These results were evaluated and compared to the true volume and the known motion amplitude. Regarding the credentialing of radiotherapy delivery, three treatment plans were made by institutions based on the two targets static 3D-CTs and using the 4D-CT data set of the 15 mmd animated by the 20 bpm/15A signal. Prior to phantom measurements, a beam output check was performed in water under reference conditions for the institution chosen energy. The plans were then measured twice using EBT3 films (12.5 cm × 5 cm) and a 0.04cc ionization chamber (Scanditronix/Wellhoffer Inc.). The films analysis was done in RIT113 version 6.3. Gamma analyses were performed using film dose as reference, a normalisation at the centre of the sphere, a dose threshold at 20%Dmax and 3% dose/3 mm deviation as agreement criteria. Results: On average volume deviations (here expressed in % of the true volume) were respectively for the 15 mmd and the three motions tested: +10% (±7%), + 1% (±17%), +12% (±12%) and for the 25 mmd: +6% (±7%), +4% (±7%). Volume deviations were found higher at the end of inspiration than at the end of expiration 8% (±26%) insp and 1% (±3%) exp. The range of motion was underestimated in all cases of in average −0.15 cm (±0.07 cm), the slow breathing pattern (10 bbpm) presented the largest mean error −0.2 cm (±0.2 cm) compared to the breathing pattern 20 bpm/15A, −0.09 cm (±0.08 cm). Regarding the dosimetric evaluation, the output dose mean deviation was 0.57% (±1.42%) across institutions, agreement between chamber doses and point-planned doses were respectively for the 15 mmd and the 25 mmd static 98.9% (±1.3%), and 99.9% (±2.8%). Agreement with planned dose (centre of the PTV taken as reference point) for the 15 mmd in motion was 98.6% (±0.86%). The film gamma mean pass rates were 70% for15 mmd static, 59% for 15 mmd dynamic and 74% for 25 mmd static. Conclusion: QA of stereotactic treatments on a moving target are not yet practice routine, film dosimetry in 4D conditions can be challenging due to the absence of a consortium on where the films should be registered to the planned dose. Moreover we lack of consistent data to define an acceptability threshold. These preliminary results are a starting point for discussion, with more dataset analysed we hope to correlate 4DCT and dosimetric data and to propose relevant evaluation criteria.